PENGARUH MODEL PEMBELAJARAN QUESTIONING TERHADAP MOTIVASI BELAJAR SISWA - Harun Pradana; Mujiburrahman Mujiburrahman (UNDIKMA, 2019)
Questioning learning model is a method of learning that is done by submitting questions that lead students to understand the subject matter in order to achieve learning goals. The purpose of this study was to determine the effect of the Questioning learning model on student learning motivation in Class VIII Social Sciences 2 Madapangga Integrated Social Studies subjects in Bima District 2018/2019 academic year. The population in this study was the eighth grade students of SMPN 2 Madapangga, Bima, which amounted to 207 students. The sample used in this study was 24 students. Data collection methods used in the form of questionnaires and documentation. To analyze data using Chi-Square, based on chi count data analysis of 0.61 with a chi table value of 15.507 at a significance level of 5%. Thus the chi count value is smaller than the chi table value (0.61 <15.507), so it can be concluded that there is the influence of the questioning learning model on students' learning motivation in integrated social studies class VIII at Madapangga 2 Junior High School Bima District 2018/2019 , and the results of this study were declared significant.